WSN based Soil Moisture Stress Monitoring and identifying its association on Other Parameters on plants growth using hadoop Framework - Sunil Kumar, S; Nagesh, HR (International Journal of Computer Sciences and Engineering, 2025)
Nowadays farmers are facing huge difficulties in their cultivation and don’t get expected yields due to several diseases caused by many factors such as unpredictable changes in weather and soil parameters. This problem leads to research in the area of agriculture towards precision agriculture with an intention of improving the crop yield. The lots of research works are underway on precision agriculture. In this regard, this paper present research work of study on how soil moisture affects the growth of tomato plant and its association among other soil parameters such as temperature, pH etc